2022
DOI: 10.1037/pas0001069
|View full text |Cite
|
Sign up to set email alerts
|

To be fooled or not to be fooled: Approach and avoidance facets of Machiavellianism.

Abstract: The antagonistic personality trait Machiavellianism (Mach) should be characterized by duplicity, proclivity to manipulation, cynical disregard of others, long-term planning, and low aggression. Opposed to theoretical descriptions, recent studies revealed links between Mach and neuroticism, impulsivity, and aggression. The advantages of a multidimensional assessment of Mach are well known but were seldom implemented. Hence, differential effects within Mach have often been neglected. Based on previous research o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(74 citation statements)
references
References 62 publications
2
72
0
Order By: Relevance
“…Arguably, in the sense of psychological distance, those engaging in CB find it "easier" to dehumanize others since they have only limited sensory contact and hence only limited cues of the agony felt by the victims (Bastian et al, 2012;Graf et al, 2022). Given that Mach refers to cynical views of humanity and antagonism (Blötner & Bergold, 2022;Christie & Geis, 1970), we proposed that low compassion for others enables individuals high in Mach to view others as manipulable and exploitable means to an end. This view should promote dehumanizing tendencies (Sijtsema et al, 2019).…”
Section: Dehumanization As a Mediator Between Machiavellianism And Bu...mentioning
confidence: 98%
See 4 more Smart Citations
“…Arguably, in the sense of psychological distance, those engaging in CB find it "easier" to dehumanize others since they have only limited sensory contact and hence only limited cues of the agony felt by the victims (Bastian et al, 2012;Graf et al, 2022). Given that Mach refers to cynical views of humanity and antagonism (Blötner & Bergold, 2022;Christie & Geis, 1970), we proposed that low compassion for others enables individuals high in Mach to view others as manipulable and exploitable means to an end. This view should promote dehumanizing tendencies (Sijtsema et al, 2019).…”
Section: Dehumanization As a Mediator Between Machiavellianism And Bu...mentioning
confidence: 98%
“…Although positive links between Mach and overt aggression oppose theoretical considerations regarding Mach, respective findings have emerged quite consistently (e.g., Vize et al, 2018). To explain such counterintuitive findings, Blötner and Bergold (2022) suggested that aggression can occur in Mach and attributed (overt) violence to Machiavellian avoidance. Their conceptualization suggests that, given a threat to one's resources or goals, individuals high in Machiavellian avoidance employ any means necessary to restore desired states or to prevent loss.…”
Section: Bullying Perpetration and Machiavellianismmentioning
confidence: 99%
See 3 more Smart Citations